IMPORTANCE AND PROSPECTS OF THE HORTICULTURE SECTOR IN AGRICULTURE OF SURKHANDARYA REGION (Scientific journal of the Fergana State University, 2025)
Surkhandarya region is located in the southern part of Uzbekistan and is inextricably linked with the development of agriculture and the formation of horticultural industries, as it has very favorable climatic conditions for horticulture. The region has been engaged in horticulture for a long time. Agriculture (cotton growing, wheat growing, viticulture, subtropical fruit growing) based on favorable natural geographical conditions and labor resources is well developed in the region. The processing of fruit and vegetable products is one of the underdeveloped sectors in the region, and it is important to increase the share of industrial products of the region due to horticulture, especially citrus fruit processing. The prospects for fruit growing are high in mountainous and foothill regions, especially export-oriented products such as pomegranates, grapes, apples and apricots are grown in large quantities. In this regard, several factors affect the development of the regional economy and horticulture. The increase in fruit and vegetable processing enterprises in the region contributes to the creation of added value and an increase in export indicators.It is important to make additional investments in the production of dried fruits, sweets, and juices. This is due, firstly, to the fact that cotton ginning plants are not operating at full capacity due to a decrease in cotton yield, and secondly, to the lack of industrial enterprises processing fruits, grapes, and other products. Expanding scientific research in the field of horticulture, training farmers and workers in modern methods will increase the competitiveness of the region.The article discusses the attention paid to the field of horticulture in Surkhandarya region, its achievements and shortcomings, and provides suggestions and recommendations. It is clear from this that citrus fruits can be used in the medical field. The proper use of favorable agro-climatic resources in our region is considered beneficial for our people. The prospects for the horticulture sector in Surkhandarya region are great. The use of modern technologies, strengthening the region's export potential, and the production of ecological products will be of great importance in the future development of the region.